'Eye for an eye, and tooth for tooth' - in search for lasting peace in Southern Africa - Mwandayi, Canisius (Midlands State University, 2016)
The history of our motherland Africa has been characterised by numerous and complex ups and downs. the greater part of the journey, however, which Africa has travelled, is marked with tears. this paper evaluates efforts which have been made to try and wipe these tears. noting some weaknesses in the peace initiatives that have been put in place to find lasting peace on the continent, the paper proposes to evoke the age-old biblical injunction: 'eye for an eye, tooth for tooth (Lev. 24:20; Dt. 19:21) as the effective route to bring lasting peace to Africa, and Southern Africa in particular.